Materials Engineering Strategies to Control Metal Oxides Nanowires Sensing Properties. Issue 12 (5th December 2021) - Kaur, Navpreet; Singh, Mandeep; Comini, Elisabetta
Abstract: Metal oxides (MOXs), in the form of nanowires, have proved to be an excellent active sensing layer of chemoresistive sensors due to their unique physical/chemical properties such as single crystallinity, exceptional electrical properties, and so on. Indeed, MOXs nanowires‐based gas sensors show fast dynamic response with excellent reproducibility, stability, and reactivity toward various gas analytes. However, their limited selectivity and high operation temperature that lead to high power consumption are still major issues that need to be addressed. To improve these characteristics, researchers nowadays are working in the direction of modifying nanowires with different strategies. These strategies include nanowires heterostructures, decoration with particles (metals and metal oxides), core–shell structures, and surface functionalization with self‐assembled monolayers and modification with graphene (pristine and oxidized). By employing these strategies, nanowires sensing performances, especially their selectivity, sensitivity, and response, can immensely enhance. Hence, in this review article, the above‐mentioned strategies to improve the sensing performance of MOXs nanowires are reviewed. Attention is paid to underlying sensing mechanisms and improved sensing characteristics. In addition, MOXs gas sensing mechanism, working principle of conductometric gas sensors, and different synthesis techniques, used to modify nanowires, are also briefly discussed. Abstract : Since last two decades, nanostructured metal oxides (MOXs) are extensively explored for gas sensing applications. In particular, MOXs nanowire‐based conductometric gas sensors show superior performance due to their unique physical/chemical properties. To further enhance their performance, researchers are modifying nanowires via different engineering strategies which are reviewed in this article.